EFFECTS OF ORGANIC AND INORGANIC NITROGEN ON THE PRODUCTIVITY OF COCONUT GROWN ON THREE IMPORTANT SOIL TYPES IN LEYTE, PHILIPPINES - M.E. Baliad (International Coconut Community, 1993)
Severe nitrogen‑deficiency in unfertilized plots resulted in low bearing percentage (19.62%) of the palms. Highest bearing percentage of 68.82% was observed on palms applied with 1.5 kg ammonium sulfate per palm per year. Application of 2 kg ammonium sulfate/palm/year resulted in most number of harvested nuts. The yields of palms applied with 1.5 kg ammonium sulfate or 0.66 kg/urea/palm/year were, however, not statistically different from the former. Similar trends in fresh meat and copra yields were observed. Copra yields were significantly higher in plots applied with inorganic N fertilizers.